'Do You Accept This Novel?': Takahashi Gen'ichirō's Koisuru genpatsu and the Violence of 'Correct' Language in Post-Fukushima Japan. Issue 2 (4th May 2017) - Tokita, Tamaki
ABSTRACT: Following the March 2011 Tōhoku earthquake, tsunami and the subsequent nuclear meltdowns in Fukushima (referred to collectively as '3.11'), critical discourse in Japan has become increasingly tense. Public debate about nuclear power has polarized society, and commentators, as well as ordinary citizens, are pressuring each other to choose between two ideological extremes. With this stifling atmosphere in the intellectual world, fiction has become an important creative venue outside the constraints of other written publications, such as non-fiction and journalism. The fictional aspect of what is known as '3.11 literature' allows authors to express their opinions freely, portraying a side of Japanese society that does not appear in mainstream media. One such author is metafiction writer Takahashi Gen'ichirō, who spearheaded these fictional responses to 3.11 with his 2011 novel, Koisuru genpatsu (A Nuclear Reactor in Love). Through an analysis of this text, I will argue that this seemingly playful, experimental and at times even offensive work contains a serious exposé of problems confronting literary and political expression in post-3.11 Japan.